2022
DOI: 10.1002/hep.32574
|View full text |Cite
|
Sign up to set email alerts
|

PP2 protects from keratin mutation–associated liver injury and filament disruption via SRC kinase inhibition in male but not female mice

Abstract: Background and Aims: Hepatocyte keratin polypeptides 8/18 (K8/K18) are unique among intermediate filaments proteins (IFs) in that their mutation predisposes to, rather than causes, human disease. Mice that overexpress human K18 R90C manifest disrupted hepatocyte keratin filaments with hyperphosphorylated keratins and predisposition to Fas-induced liver injury.We hypothesized that high-throughput screening will identify compounds that protect the liver from mutation-triggered predisposition to injury. Approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…One potential benefit of identifying uniquely functioning drugs that may have clinical utility in keratin-and other IF-related disorders is that they may offer the opportunity to be used, after testing experimentally, as combination drugs. This applies to the demonstrated protective effect in keratin mutants by 2 separate Ser/Thr or Tyr kinase inhibitors (17)(18)(19) and the observation herein by targeting protein acetylation. Such an approach is likely to be particularly beneficial for drugs that are already in clinical use and, therefore, can be repurposed for keratin-and other IF-related disorders.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…One potential benefit of identifying uniquely functioning drugs that may have clinical utility in keratin-and other IF-related disorders is that they may offer the opportunity to be used, after testing experimentally, as combination drugs. This applies to the demonstrated protective effect in keratin mutants by 2 separate Ser/Thr or Tyr kinase inhibitors (17)(18)(19) and the observation herein by targeting protein acetylation. Such an approach is likely to be particularly beneficial for drugs that are already in clinical use and, therefore, can be repurposed for keratin-and other IF-related disorders.…”
Section: Discussionmentioning
confidence: 69%
“…A total of 24 compounds were selected from the initial screening (performed in 384-well plates) for validation using chamber slides, with transduced A549 cells treated with the 24 compounds. From these compounds, PP2 (19) and PN had the most prominent effect in terms of decreasing the extent of K18-R90C filament collapse and dot formation. Further validation was then carried out by testing the dose response for PN (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SFK activity and downstream signalling has previously been implicated in the progression of a number of liver disorders including hepatocellular carcinoma 44 and liver fibrosis 45 . In addition, a role for c-SRC in cell fate determination during endodermal commitment of human iPSCs has recently been described 46 , the kinase inhibitor PP2 has previously been shown to protect against Keratin mutation-induced mouse liver injury through Src inhibition (Li et al, 2023), and previous studies have demonstrated that genetic deletion of Src's binding partner focal adhesion kinase (FAK) accelerates liver regeneration 48 . It is our understanding that ours is the first study to demonstrate a role for small molecule SFK inhibitors in the promotion of hepatocyte progenitor differentiation and as a potential therapeutic opportunity for liver regeneration.…”
mentioning
confidence: 99%